Sir Robert Peel's Bank Act of 1844 explained and defended - Hancock, W. Neilson (Dublin Statistical Society, 1856)
THERE are few acts of parliament more important in themselves, or which have given rise to more discussion, than Sir Robert Peel's celebrated Bank Act of 1844 (7 and 8 Victoria, cap. 32). I am anxious to take an opportunity of expressing my strong opinion in favour of the provisions of that act, and to explain at the same time the scientific grounds on which that opinion rests.
Read December 17th, 1855
Keywords: Bank Act, 1846; 314.15